Tinjauan Yuridis Terhadap Putusan Bebas Dalam Tindak Pidana Pencemaran Nama Baik di Media Sosial - Sasmita Sasmita; Hasuri Hasuri (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2023)
When a criminal case is resolved in court, the public expects legal certainty and justice regarding the resolution of the case, namely the Judge's Decision. In the Criminal Procedure Code, only the term